Antibiotic Resistance Genes in Salmonella Isolates from Food Production Environments and Clinical Sources in the Middle East: A Systematic Review and Meta-Analysis Revealing the Limited Comparative Genomic Evidence - Mohammad Al-Hasan; Ahmad Al-Dhumair; Hanan Al-Khalaifah; Nazima Habibi; Qadreyah Almatawah (Life, 2026)
This systematic review collects available evidence on genetic similarities between antibiotic resistance genes (ARGs) in Salmonella isolates collected from both food production environments and hospitalized patients in the Middle East (ME) region. We conducted an extensive search across PubMed, ScienceDirect, Scopus, Web of Science, and Google Scholar, following PRISMA guidelines, to cover all available literature up to May 2026. Finally, 94 studies met our inclusion criteria. Overall pooled prevalence of Salmonella isolates was 0.30 (95% CI: 0.23–0.36, p < 0.001, I2 = 99.92%). The prevalence of specific classes (β-lactamases [ESBLs], quinolones, chloramphenicol, aminoglycosides, and tetracyclines) was 0.49 (95% CI, 0.31 to 0.66, p < 0.001, I2 = 98.47%). Our findings further demonstrate a high diversity of classes, with β-lactamase genes (blaTEM, blaCTXM, blaSHV, blaCMY, blaOXA, and blaNDM), which were most commonly detected across the ME region in the food production environment and clinical isolates 0.48 (95% CI, 0.37 to 0.58, p < 0.001, I2 = 99.34%). Although studies have documented resistance against different classes in both food production environments and clinical Salmonella isolates in the ME, however, the direct comparative genomic evidence demonstrating genetic similarity and transmission between these sources is still missing. Further research is needed to investigate the application of WGS to directly compare isolates from food production environments and clinical isolates within the same geographic areas.